If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -2x = 17 + 2x Solving 25 + -2x = 17 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 25 + -2x + -2x = 17 + 2x + -2x Combine like terms: -2x + -2x = -4x 25 + -4x = 17 + 2x + -2x Combine like terms: 2x + -2x = 0 25 + -4x = 17 + 0 25 + -4x = 17 Add '-25' to each side of the equation. 25 + -25 + -4x = 17 + -25 Combine like terms: 25 + -25 = 0 0 + -4x = 17 + -25 -4x = 17 + -25 Combine like terms: 17 + -25 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 11x+7y=2 | | 8n=-160 | | (5x+8)-(7+4y)=8 | | 5=x-17 | | 24=6(5-2a) | | -29=-25+r | | 0=1600-60x | | -9=m-(-5) | | -9/12-(-7/4) | | 7y-3x= | | 15x+(-4x)= | | 1/7*1/6 | | 2xy/5y | | -480=20x | | 4-p=5p+16 | | 522=29x | | 4x+5-2x=-19 | | 3[4x-(2x-7)]= | | a/1/a2= | | 1=v-(-12) | | 5x+12=3x-23 | | 8/9*(-1/8)= | | -3+a=26 | | -5(1+5n)=120 | | (5x+2)(5x-1)=0 | | 3x+y-4x= | | 2(2x-7)+3x=21 | | 3p-6=6 | | -2=n-16 | | 8x+2x-4=126 | | (5x+5)-(2+4x)=5 | | y=3x^2-14x+12 |